A skirmish on the Czech political scene: The glocalization of Greta Thunberg's UN Climate Action Summit speech in the Czech media. (December 2021) - Homoláč, Jiří; Mrázková, Kamila
Highlights: Thunberg's speech is denied relevance through the categorization of her as a person. The use of SNS posts blurs the border between media and everyday discourse. A global phenomenon can be glocalized through a media dialogical network. Glocalization can take a form of a polemic with other local recontextualizations. Abstract: This article is devoted to the local reconfiguration of global discourse. Utilizing the concepts of media dialogical network, membership category and glocalization, it analyses the development of the global media dialogical network initiated by Greta Thunberg's speech at the UN Climate Action Summit in September 2019 in reports by the Czech News Agency, on the web page of the most widely read Czech tabloid newspaper, and in public television programs. The analysis focuses on the ways in which the social network siteś posts were integrated into the given media dialogical network, the categorization of Thunberg and the forms of glocalization of her speech. Through the social network siteś posts by Czech politicians, either those quoted or presented merely in the form of unattributed summaries, dominant categorizations of Thunberg were introduced into the given media dialogical network, especially those which disqualified her as a person and thus her speech as well. The way in which the social network siteś posts were used also significantly influenced the degree and manner of glocalization of this speech.